Long - Term Effects of Topical Amniotic Membrane Stem Cell Metabolite Product (AMSC-MP) and Fractional CO2 Laser in Photoaging - Dyah Ayu Pitasari; Afif Nurul Hidayati; Muhammad Yulianto Listiawan; Sawitri Sawitri; Damayanti Damayanti; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Photoaging causes wrinkles, lentigines, keratoses, dyspigmentation, telangiectasia, decreased elasticity, rough texture, and pale color. Facial wrinkles and mottled skin can negatively affect perceived attractiveness, self-esteem, personality, and level of acceptance. Stem cells are important cells in the skin, and they are the source for continuous regeneration of the epidermis. It can be extracted from many sources, including amnion. Amnion membrane stem cell (AMSC) can be cultured and secretes metabolite product, and it can rejuvenate aging skin. Laser-Assisted Drug Delivery (LADD) involves selective destruction of the layers of the epidermis and dermis to allow penetration and absorption of topical drugs as well as large molecular weight drugs such as stem cells. Purpose: To evaluate the long-term effects of topical administration of AMSC metabolite products (AMSC -MP) and fractional CO2 laser on the clinical improvement of photoaging compared to previous skin conditions. Methods: This was an observational study which was aimed to evaluate the long-term effects of clinical improvement after topical therapy of AMSC-MP and fractional CO2 laser in patients with photoaging. Results: The results of the analysis showed a decrease in wrinkles, dark spots, skin tone, and pores. Conclusion: Based on Janus-II® assessment, there was improvement degrees of wrinkles, dark spots, and pores in patients with photoaging who received fractional CO2laser fractional for 12 weeks. There were no side effects found in this study.